Vibration characteristics of carbon-fiber reinforced composite drive shafts fabricated using filament winding technology. (1st June 2020) - Sun, Zeyu; Xiao, Jie; Yu, Xuduo; Tusiime, Rogers; Gao, Hongping; Min, Wei; Tao, Lei; Qi, Liangliang; Zhang, Hui; Yu, Muhuo
Abstract: The metal connector and tube of the composite drive shaft were bonded together generally. However, the glued shafts showed numerous risks due to the instability of chemical glues. To avoid potential risks, filament winding with integrated flanges was proposed to prepare carbon fiber-reinforced composite (CFRP) drive shafts in this study. The natural frequency and damping of CFRP shafts were investigated by FEA and experiment. Results revealed that the natural frequency of CFRP shafts embedded in metal flanges is slightly lower than that of the glued CFRP shafts. The metal flanges did not affect the changing trend of the natural frequency with various fiber ply angles or thicknesses, and the damping had little effect on the natural frequency. The natural frequency of CFRP tubes and drive shafts was predicted using FEA and agreed well with the experimental results. The results of this study will be of great significance in the design and application of CFRP drive shafts.